Recovery of 15N in the banana plant within sediment origin soil. - Acón-Ho, Jorge (2013)
Between October, 2003 to February, 2004 at the Finca Venecia, located in Matina in Limón, mobility in soil and recovery of banana plant nitrogen was determined, using the direct method with 15N isotopic method. Three sources enriched with 15N: urea (U), ammonium nitrate (NA) and ammonium sulfate (SA) were evaluated, at a dosage of 424 kg N per hectare per year and “monitored” through profile at four depths: 10, 30, 60 and 90 cm of soil and four growth stages (start, F10, Fm, flowering and harvest) of banana cultivation. Forms of N available from the SA was determined in greater quantity in the soil and in lesser amounts in tissues of the plant, indicating a lower tendency to be lost or absorbed from the system than the other sources. Urea is the nitrogen source that produces the greatest accumulation of N in the fruit and positively affects the plant dry weight, compared with other nitrogen sources tested (NA and SA). The use of SA appears to have a negative effect on the growth of the mother and offspring rhizome so its use as the sole source of N fertilization is not recommended. Such situation may indicate the need to use a fertilizer where the total concentration of N, comes from a mixture of several sources.